2018
DOI: 10.3389/fendo.2018.00152
|View full text |Cite
|
Sign up to set email alerts
|

Tributyltin and Zebrafish: Swimming in Dangerous Water

Abstract: Zebrafish has been established as a reliable biological model with important insertion in academy (morphologic, biochemical, and pathophysiological studies) and pharmaceutical industry (toxicology and drug development) due to its molecular complexity and similar systems biology that recapitulate those from other organisms. Considering the toxicological aspects, many efforts using zebrafish models are being done in order to elucidate the effects of endocrine disruptors, and some of them are focused on tributylt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 66 publications
3
3
0
Order By: Relevance
“…For instance, arsenic showed increased locomotor activity [98] and tributyltin significantly reduced the locomotor activity [103] in zebrafish larvae. These effects were similar to that described in the rodent models where arsenic is shown to cause an increase in locomotor activity [98] and tributyltin is shown to cause a dose-dependent decrease in spontaneous motor activity [117]. Thus, the light-dark locomotion test in zebrafish larvae has been successfully employed for the study of neurobehavioral alterations caused by various environmental toxicants.…”
Section: Identification Of Neuroactive Compoundssupporting
confidence: 74%
“…For instance, arsenic showed increased locomotor activity [98] and tributyltin significantly reduced the locomotor activity [103] in zebrafish larvae. These effects were similar to that described in the rodent models where arsenic is shown to cause an increase in locomotor activity [98] and tributyltin is shown to cause a dose-dependent decrease in spontaneous motor activity [117]. Thus, the light-dark locomotion test in zebrafish larvae has been successfully employed for the study of neurobehavioral alterations caused by various environmental toxicants.…”
Section: Identification Of Neuroactive Compoundssupporting
confidence: 74%
“…On the other hand, our results also showed TBT effects in genes implicated in lipid metabolism and fatty acid biosynthesis pathways, which is consistent with an observed lipidic disruption previously reported in similar experimental setups (den Broeder et al, 2017). However, lipid dysregulation took place only at relatively high TBT concentrations, and it was limited to the transcriptomic level (Berto-Júnior et al, 2018;Grün, 2014;Ouadah-Boussouf and Babin, 2016;Tingaud-Sequeira et al, 2011). The induction of yolk-sac malabsorption syndrome or energy consumption dysregulation by TBT has not been found at this stage of development (5 dpf) (Liang et al, 2017;Martínez et al, 2019a), and J o u r n a l P r e -p r o o f obesogenic effects only appear at later larval stages (15 dpf, (den Broeder et al, 2017)).…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, TBT has also been described as an antagonist of human ERs by inhibiting the transcriptional activation of the ER-dependent reporter gene and the interaction between the ligand-binding domain of the β isoform (ERβ LBD) and the steroid receptor coactivator-1 (SRC1) [ 58 , 59 ]. Additionally, TBT acts as an inhibitor of aromatase, the enzyme accountable for the conversion of testosterone to estrogen, as well as the estrogen receptor in zebrafish, thereby reducing the effects of ethinylestradiol [ 60 ]. Additionally, numerous studies have revealed that TBT disrupts estrogen signaling, affecting various tissues, as shown in Figure 1 [ 28 , 30 , 33 , 61 , 62 , 63 , 64 , 65 ].…”
Section: Introductionmentioning
confidence: 99%